Meningkatkan Minat Membaca Siswa Sd N 2 Gadingsukuh Kelas Ii Menggunakan Metode Struktural Analitik Sintetik (Sas) - Solikhati Khasanah (Prosiding University Research Colloquium, 2021)
This study aims to increase interest in reading by using the SAS method in second gradestudents of SD Negeri 2 Gadingsukuh. This research was conducted using classroom actionresearch. The subjects of this research were second grade students of SD Negeri 2Gadingsukuh Semester II for the 2020/2021 Academic Year, totaling 10 students. In thisstudy using the SAS method. The techniques used in this research are: 1) scale, 2)observation, and 3) documentation. The data analysis technique used descriptive,quantitative, and qualitative analysis. The results of the study indicate that the readinginterest of the second grade students of SD Negeri 2 Gadingsukuh can be increased byusing the SAS method. In the pre-action, the percentage of students who have a minimumamount of reading interest has reached a good predicate of 0%. In the first cycle the numberof students who have reached an average value of 61. In the second cycle the number ofstudents who have achieved an increase with an average value of 79. Learning using theSAS method has increased in the second cycle.